2013
DOI: 10.3892/etm.2013.1031
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of sequential therapy by electric coagulation, cryotherapy and balloon dilation with an electronic video bronchoscope

Abstract: The aim of the current study was to retrospectively analyze clinical data concerning bronchostenosis or bronchial obstruction caused by endobronchial tuberculosis. Fifty-six cases were subjected to bronchoscopy and chest computed tomography to assess the prognosis of bronchostenosis and bronchial obstruction. Based on reliable and effective anti-pulmonary tuberculosis therapy, these conditions were treated sequentially by electric coagulation, cryotherapy and balloon dilation with an electronic video bronchosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 28 publications
0
4
0
3
Order By: Relevance
“…Recently, cryotechnology has been utilized for several therapeutic purposes in bronchology including endobronchial cryodebridement procedures for endobronchial tuberculosis, tracheal strictures, endobronchial fibrosis, removal of broncholith, cryosurgery for lung cancer and in immediate debulking of endobronchial tumours (cryorecanalization) . Cryosurgical equipment operates by the Joule–Thomson effect, where a compressed gas released at high flow rapidly expands and creates a very low temperature at the tip of the probe.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, cryotechnology has been utilized for several therapeutic purposes in bronchology including endobronchial cryodebridement procedures for endobronchial tuberculosis, tracheal strictures, endobronchial fibrosis, removal of broncholith, cryosurgery for lung cancer and in immediate debulking of endobronchial tumours (cryorecanalization) . Cryosurgical equipment operates by the Joule–Thomson effect, where a compressed gas released at high flow rapidly expands and creates a very low temperature at the tip of the probe.…”
Section: Introductionmentioning
confidence: 99%
“…• Muerte: se describe una mortalidad en 30 a 60 días con CBPTB de 0,7 %, mucho menor que la descrita para VATS (1,8%), y en caso de EPID asociada a exacerbación 11,17,26 . Varía en caso de lesiones obstructivas de la vía aérea, con una mortalidad a 30 días de 7,1%, cuyas principales causas fueron hemoptisis y falla respiratoria, relacionando la progresión de la enfermedad tratándose de neoplasia 31 .…”
Section: Complicaciones De La Criobiopsiaunclassified
“…Cuando se comparó la CBPTB con la biopsia transbronquial, los diagnósticos histopatológicos fueron mucho mayores en el grupo de criobiopsia; 74,4% vs 34,1% con una diferencia estadísticamente significativa (p < 0,001), al igual que el rendimiento diagnostico 51,3% vs 29,1% (p = 0,038). El área de las biopsias obtenidas por CBPTB fue mucho mayor 14,7 ± 11 mm 2 que las obtenidas con fórceps 3,3 ± 4,1 mm 2 con diferencia significativa [31][32][33] .…”
Section: • Criobiopsia Vs Biopsia Transbronquial Con Fórceps (Convencunclassified
See 1 more Smart Citation
“…Biopsy via cryoprobe, rst used in 1968, has mainly been employed in the management of obstructive endobronchial tumors. Recently, cryotherapy in bronchoscopy has been used for several purposes including management of endobronchial tuberculosis [10], endobronchial tumors [11][12][13], for diagnosis of interstitial lung disease (ILD) [14][15][16][17], and peripheral lung lesion [18]. ese studies have demonstrated that the cryoprobe is feasible and a more e cient diagnostic tool with a superior diagnostic rate and ability to obtain a larger specimen with better preserved cellular architecture than forceps biopsy.…”
Section: Introductionmentioning
confidence: 99%